PENENTUAN HARGA JUAL PRODUK DENGAN METODE COST PLUS PRICING DALAM PERSPEKTIF ISLAM - Moh Helmi Hidayat (Al-Amien Prenduan for Islamic Institute, 2020)
The rise of the halal life style or the halal lifestyle opens up great opportunities for related business people, especially those in the Al Khudaifi Muslim koko clothing business in Pamekasan Madura. This also provides da'wah opportunities for actors in the Islamic economy. Islam teaches humankind to cooperate in economic activities so that it is mutually beneficial. The variable costing method, the cost of production which is calculated in the calculation of the cost of goods manufactured is only composed of variable production costs, namely raw material costs, direct labor costs, and factory variable overhead costs. The purpose of this study is to determine and analyze the cost plus pricing method in Al-Khudaifi's confectionery business in Pamekasan Madura in Islamic terms and the benefits of implementing cost plus pricing. This study uses descriptive qualitative research methods, namely research that describes data and information based on facts obtained in the field regarding production costs and production prices in the Al-Khudaifi Pamekasan Madura confection business. The results of this study indicate that the calculation of the selling price of Al-Khudaifi -Khudaifi with the cost plus pricing method only takes into account the elements of production costs, while non-production costs are not taken into account. In determining the selling price of the cost plus pricing method, all elements of production costs are calculated to be total costs, after which add a mark up of 15% of the total production. The determination of product prices in the Al-Khudaifi Confection business is not in the context of lowering the market prices that have been established in the community so as not to harm other traders. Suggestions for Al-Khudaifi's confection must be correct in setting the selling price. Competitive selling prices in the market will have an impact on the ups and downs of interest in selling an item. Entrepreneurs need to carry out an evaluation in determining product prices, both old prices and new prices. For business continuity, the business owner considers how to determine the selling price of the product based on cost plus pricing, where the selling price that is determined includes all costs that are budgeted for expenses and the level of profit will be obtained.